2017
DOI: 10.3945/an.116.013748
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Smartphone Applications for Nutrition Improvement in Community Settings: A Scoping Review

Abstract: Smartphone applications are increasingly being used to support nutrition improvement in community settings. However, there is a scarcity of practical literature to support researchers and practitioners in choosing or developing health applications. This work maps the features, key content, theoretical approaches, and methods of consumer testing of applications intended for nutrition improvement in community settings. A systematic, scoping review methodology was used to map published, peer-reviewed literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 93 publications
(316 reference statements)
2
24
0
1
Order By: Relevance
“…This suggests that it would be useful to use the Transtheoretical Model alongside TPB to structure app content and features to cater for users at all stages of the behavior change cycle, particularly features that draw participants in, despite a lack of intention to change target behaviors. One option to engage this group of users is the inclusion of games with an inherent educational element, with games commonly being used in apps targeted toward low socioeconomic status and adolescent populations to enhance engagement [ 2 , 51 , 52 ]. During all stages of this research, it was demonstrated that even simple quiz games were enjoyed, consistent with findings from others [ 53 - 55 ], and in this, participant group games were the second most common reason for phone use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that it would be useful to use the Transtheoretical Model alongside TPB to structure app content and features to cater for users at all stages of the behavior change cycle, particularly features that draw participants in, despite a lack of intention to change target behaviors. One option to engage this group of users is the inclusion of games with an inherent educational element, with games commonly being used in apps targeted toward low socioeconomic status and adolescent populations to enhance engagement [ 2 , 51 , 52 ]. During all stages of this research, it was demonstrated that even simple quiz games were enjoyed, consistent with findings from others [ 53 - 55 ], and in this, participant group games were the second most common reason for phone use.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to conducting this study, a scoping review [ 2 ] was performed to identify best practice methods for app development and end-user testing. The scoping review identified numerous app features that were successfully used to promote app engagement in adolescents, young adults and disadvantaged communities that were applicable to this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Num contexto de reaprendizagem, as novas tecnologias são incorporadas no dia a dia como "importantes ferramentas" no processo de controle de si, instrumentalizadas para fomentar a promoção da "boa saúde". 39 A proposta de "educar de novo" ou "reeducar" como a abertura de um caminho para uma nova ordem alimentar está, em grande medida, fadada ao insucesso ao não romper com um discurso normativo e impositivo, como já apontado anteriormente. É preciso compreender que além da necessidade biológica inerente à manutenção da vida, "comemos" de acordo com uma organização social e de acordo com uma determinada forma de produzir e distribuir alimentos, "comemos" de acordo com nossos grupos e classes de pertencimento.…”
Section: ) àS Vezes Quando Não Tem Pão Eu Tomo Café Puro Até Que é unclassified